FINANCIAL POLICY OF BUSINESS ENTITIES: ESSENCE AND STAGES OF FORMATION (INNOVATIVE ECONOMY, 2025)
Shuliuk B.S., Snihur I.R.  FINANCIAL POLICY OF BUSINESS ENTITIES: ESSENCE AND STAGES OF FORMATIONPurpose. The aim of the article is to systematize the stages of forming the financial policy of business entities and to identify the corresponding tools for each stage of its implementation.Methodology of research. The study employs a systemic approach as the general methodological foundation. The method of systems analysis is applied to consider financial policy as an integrated management system; structural-functional analysis is used to isolate key elements of the policy and their interrelations; logical analysis is applied to construct the sequence of its formation stages. Methods of abstraction and generalization are used to analyse scientific approaches to the concept of “financial policy.” Comparative analysis is employed to compare approaches to forming financial policy at the enterprise and state levels, as well as across different types of business entities.Findings. Scientific approaches to the concept of “financial policy” are analysed. The necessity of phased formation of financial policy as a complex management system is substantiated, along with the advisability of distinguishing it from state financial policy and taking into account the specifics of different types of business entities. Seven key stages are identified: methodological justification, financial condition diagnosis, goal setting, tool selection, organizational implementation, monitoring and control, adaptation and improvement. For each stage, goals, tasks, and relevant management tools are outlined. It is established that the implementation of financial policy requires adaptation to the scale, organizational and legal form, and resource capabilities of the enterprise.Originality. The author proposes a model of financial policy formation based on a staged system with feedback mechanisms, ensuring its flexibility, goal orientation, and stability. The interpretation of the term “financial policy” is deepened in the context of a systems approach.Practical value. The proposed model can be used by managers of commercial and non-profit organizations, as well as financial analysts, to create an effective financial policy aligned with the overall organization's strategic goals in a dynamic environment.Key words: financial policy, business entities, financial management, financial strategy.
Keywords: financial policy; business entities; financial management; financial strategy